2018
DOI: 10.1007/s00382-018-4106-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the intensification of the upwelling-favorable winds during El Niño 1997–1998 in the Peruvian upwelling system

Abstract: The physical processes driving the wind intensification in a coastal band of ~100 km off Peru during the intense 1997-1998 El Niño (EN) event were studied using a regional atmospheric model. A simulation performed for the period 1994-2000 reproduced the coastal wind response to local sea surface temperature (SST) forcing and large scale atmospheric conditions. The model, evaluated with satellite data, represented well the intensity, seasonal and interannual variability of alongshore (i.e. NW-SE) winds. An alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…This flux reduction was partly driven by the reduction of the vertical velocity (Figure 7d), which counteracted the impact of the subsurface oxygen increase (Figure 7c). Note that the modeled vertical velocity decrease (∼40% at 50 m depth, Figure 7d) cannot be fully attributed to a decreased Ekman pumping during EN (e.g., Halpern, 2002;Chamorro et al, 2018, for the 1997-1998, as it was only ∼5% in our simulation (Figure not shown).…”
Section: Eddy Oxygen Fluxesmentioning
confidence: 69%
See 1 more Smart Citation
“…This flux reduction was partly driven by the reduction of the vertical velocity (Figure 7d), which counteracted the impact of the subsurface oxygen increase (Figure 7c). Note that the modeled vertical velocity decrease (∼40% at 50 m depth, Figure 7d) cannot be fully attributed to a decreased Ekman pumping during EN (e.g., Halpern, 2002;Chamorro et al, 2018, for the 1997-1998, as it was only ∼5% in our simulation (Figure not shown).…”
Section: Eddy Oxygen Fluxesmentioning
confidence: 69%
“…During EN, when the interannual wind variability is suppressed (in Wclim), a relatively weak subsurface oxygen increase is observed. This can be explained as follows: as the alongshore wind increases during EN (see Figure 9 in Enfield, 1981;Espinoza-Morriberón et al, 2017;Chamorro et al, 2018), the coastal upwelling intensifies. This partly compensates the ZO2 deepening, bringing deep oxygen-poor waters in this depth range.…”
Section: Remote and Local Drivers Of Do Interannual Variabilitymentioning
confidence: 99%
“…A comparable wind stress curl anomaly developed during the 1997-1998 El Niño off southern Peru near Pisco (15 • S), enhancing the downwelling primarily driven by the very intense downwelling coastal trapped waves (Halpern, 2002). The dynamical processes responsible for the 1997-1998 nearshore wind increase were recently analyzed by Chamorro et al (2018). Using a regional atmospheric model, the authors showed that the increase of nearshore wind was driven by the SST alongshore gradient, associated with the accumulation of warm waters along the northern shores of Peru.…”
Section: Discussionmentioning
confidence: 95%
“…During February and March, the Ekman pumping negative anomaly associated with the wind stress curl (Figure 2E) may have deepened the thermocline, and thus the cooling due to enhanced upwelling at the coast may have been mitigated by the upward flux of anomalously warm source waters. The atmospheric response to the SST gradient, described by Chamorro et al (2018) for the 1997-1998 El Niño, may thus feedback positively on the warming initiated in January. The ocean-atmosphere coupled processes occurring during this event would need to be more fully investigated using a regional coupled ocean-atmosphere model (Oerder et al, 2016(Oerder et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…A.2), both identified in previous in the latitude of 15°S (e.g. Belmadani et al, 2014;Chamorro et al, 2018) as part of the Pacific coastal temperature inversion. In this way, the easterly flow at higher levels does not have a direct influence on coastal circulation.…”
Section: North Of the Basinmentioning
confidence: 76%